2018
DOI: 10.1037/ort0000302
|View full text |Cite
|
Sign up to set email alerts
|

Visiting Auschwitz: Evidence of secondary traumatization among high school students.

Abstract: Secondary traumatic stress has been intensively studied among survivors' therapists, family members, and trauma researchers. We claim that people who are exposed to reminders of past traumatic experiences when visiting places of memory or museum exhibitions could also develop secondary trauma symptoms. Thus, scholars and practitioners must better understand how such places related to historical traumatization (e.g., Holocaust memorial sites) can affect the psychological well-being of visitors. The main aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…For perpetrator group members, reminders of how their group's past actions continue to harm an outgroup today can lead to defensive responses and heighten prejudice (e.g., Imhoff & Banse, 2009). Descriptions of historical trauma can cause secondary traumatic stress in learners, particularly among the highly empathic (Bilewicz & Wójcik, 2018). As well, if a person perceives an outgroup's suffering to be beyond repair, they may feel less empathy for that group (Lerner & Simmons, 1966; Starzyk & Ross, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For perpetrator group members, reminders of how their group's past actions continue to harm an outgroup today can lead to defensive responses and heighten prejudice (e.g., Imhoff & Banse, 2009). Descriptions of historical trauma can cause secondary traumatic stress in learners, particularly among the highly empathic (Bilewicz & Wójcik, 2018). As well, if a person perceives an outgroup's suffering to be beyond repair, they may feel less empathy for that group (Lerner & Simmons, 1966; Starzyk & Ross, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…τ 2 = 0.00, SE = 0.02; I 2 = 0.01%. in learners, particularly among the highly empathic (Bilewicz & Wójcik, 2018). As well, if a person perceives an outgroup's suffering to be beyond repair, they may feel less empathy for that group (Lerner & Simmons, 1966;Starzyk & Ross, 2008).…”
Section: Implications and Directions For Future Researchmentioning
confidence: 99%
“…Lastly, three quantitative longitudinal and experimental studies explored the impact of a Holocaust memorial visit for Polish, American Jewish and Israeli students. They revealed an initial increase of distress and PTSD symptoms (Bilewicz & Wojcik, 2018;Mimouni-Bloch, Walter, Ross, & Bloch, 2013;Silverman et al, 1999), but symptoms diminished to base line after twelve months (Silverman et al, 1999). Looking at emotions that are connected to PTS reactions, qualitative interview studies reveal that public commemoration nourished feelings of personal injustice, of being forgotten or misunderstood, which was linked to anger, bitterness, and resentment (Barron et al, 2008;Beristain, Paez, & Gonzalez, 2000;Burnell et al, 2010;Magierowski, 2016;Oushakine, 2006).…”
Section: Pts Reactionsmentioning
confidence: 99%
“…What has been evidenced in this study is a complex picture of the educators' descriptions of their emotional engagement with their role teaching about the Holocaust at an authentic site, both personally and professionally. In the field of museum studies, much has been written about the nature of visiting the Auschwitz-Birkenau State Museum and the emotional demands the site places upon visitors (see, for example, Bilewicz and Wojcik, 2018;Griffiths, 2018;Richardson, 2019). The current museum director has observed that even for employees who go to the site daily, 'Auschwitz overwhelms … you can never get used to it' (Cywin ´ski, 2015: 45).…”
Section: Discussionmentioning
confidence: 99%